Caracterización bromatológica de 2 variedades de alfalfa (Medicago sativa) sometida a mutación química con Ethyl Methane Sulfonate. - Macias Vera, Milta Yamilex (2024)
Alfalfa (Medicago sativa) has been present in mankind, and has managed to occupy a very important place in agriculture, this silver offers good adaptability and tolerance to moisture and drought, having a good use and a good percentage of crude protein of 22-25% with dry matter 30%. In Ecuador it has been one of the best alternatives in forage for cattle and guinea pig feeding, currently for its high protein value, having the best adaptability in the highlands. Evaluating the dose of the two types of alfalfa (improved pomegranate and national) we have as a result that the improved pomegranate alfalfa obtained better results of protein, EMS dose 0.50% obtained 23.68%, while the national alfalfa obtained 18.46% fiber the dose of 0.50% EMS 15.14%, while the national alfalfa obtained 12, The analysis of variance showed that it was not significant and the best EMS dose was 0.25% with an average of 8.72%, the lowest result was obtained with the ethyl Metasulfonate dose at 1% with an average value of 7.74% of ash, humidity the tukey test at 5% probability. The alfalfa that obtained the best result was alfalfa improved pomegranate with 76.59% moisture, the dose that obtained the lowest result was EMS 0.50% with an average of 73.44% moisture. Fat the interaction that obtained the best result was alfalfa pomegranate improved with the addition of Metasulfonate 0.75% with an average of 1.13% fat, the interaction that obtained the lowest result was national alfalfa). As a conclusion, the improved alfalfa showed a higher percentage in moisture variables at 0.75% EMS with 78.87% followed by protein at 0.25% with a value of 28.72%. National alfalfa showed a higher percentage of moisture variables at 0.50% EMS with a value of 77.45% followed by protein at 0.75% with 21.39%.